2008
DOI: 10.1097/01.won.0000313647.44870.9a
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Absorbent Dressing Specifically for Fecal Incontinence

Abstract: An anorectal dressing offers an effective, comfortable alternative to a pad for absorbing leaked feces that seems acceptable to men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…The WOC nurse specialist needs to support men in their choice of wearing an absorptive product. Bliss and colleagues 4 previously reported that a surgical gauze dressing was used by individuals with mild fecal incontinence. A few respondents in this study reported placing toilet tissue or gauze between their buttocks instead of wearing a pantiliner or pad; they tended to report leaking a small amount of loose or liquid stool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WOC nurse specialist needs to support men in their choice of wearing an absorptive product. Bliss and colleagues 4 previously reported that a surgical gauze dressing was used by individuals with mild fecal incontinence. A few respondents in this study reported placing toilet tissue or gauze between their buttocks instead of wearing a pantiliner or pad; they tended to report leaking a small amount of loose or liquid stool.…”
Section: Discussionmentioning
confidence: 99%
“…Those with mild incontinence severity, especially men, may place a small gauze dressing between the buttocks to absorb leaked stool. 4 Few absorbent products are specifically designed to absorb stool. Instead, most individuals must “make do” using products designed for urine or menstrual leakage.…”
Section: Introductionmentioning
confidence: 99%
“…33 A recent study found that a small anorectal dressing was rated highly by both men and women in the areas of soiling prevention, ability to stay in place, comfort, and overall effectiveness. 35 Most important, it provided an acceptable alternative to pads for most males, although it is more expensive. 35 Using over-the-counter oral deodorants such as bismuth subgallate or chlorophyllin copper complex may also help to decrease fecal odor.…”
Section: ■ Urge Resistance Educationmentioning
confidence: 99%
“…35 Most important, it provided an acceptable alternative to pads for most males, although it is more expensive. 35 Using over-the-counter oral deodorants such as bismuth subgallate or chlorophyllin copper complex may also help to decrease fecal odor. 32 Because anal plugs, rectal trumpets, anal bags, and internal rectal tubes are not frequently used by or readily available to communitydwelling adults, they are not discussed here.…”
Section: ■ Urge Resistance Educationmentioning
confidence: 99%
See 1 more Smart Citation